Implementation of Dijkstra Algorithm and Welch-Powell Algorithm for Optimal Solution of Campus Bus Transportation - Nurwan Nurwan; Widya Eka Pranata; Muhamad Rezky Friesta Payu; Nisky Imansyah Yahya (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2021)
This research deals with applying the Dijkstra algorithm and Welch-Powell algorithm to on-campus bus transportation problems. This research aims to determine the optimal solution of campus bus transportation routes in the shortest routes and schedules. In determining the fastest way, each intersection represented as a node, and the path described as the sides. The shortest path obtained V1 - V2 - V5 - V8 - V9 - V10 - V13 - V16. In determining the optimal schedule, the number of buses represents the vertices, and the time expresses the side that connects each node. The optimal program of the bus starts from 06.30 am to 5.00 pm. Every bus gets four sessions of departure and four sessions return with travel time each session is 60 minutes.